Failure of Ketoprofen and Interferon Combination Therapy to Improve Interferon-Resistant Chronic Hepatitis C - Frank H Anderson; Lecheng Zeng; Eric M Yoshida; Natalie R Rock (Canadian Journal of Gastroenterology)
Preliminary reports suggest that patients with interferon (IFN)-resistant chronic hepatitis C respond better to a combination of IFN-α and nonsteroidal anti-inflammatory drugs than to IFN alone. The efficacy of IFN combined with ketoprofen in the treatment of patients with IFN-resistant chronic hepatitis C was evaluated. Seventeen patients, nonresponsive after at least six months of treatment with IFN-α2b and subsequently treated with the combination of IFN-α2b plus ketoprofen for four months, were studied. Serum aminotransferases (alanine aminotransferase [ALT] and aspartate aminotransferase [AST]) and serum hepatitis C virus (HCV) RNA were analyzed before and throughout treatment. No patient normalized serum aminotransferases after combination therapy. There were no significant differences in mean serum ALT and AST levels before and after ketoprofen intervention. Serum HCV RNA became undetectable after treatment in only one patient, but was detectable again three months after treatment cessation. These results provide no convincing evidence that the combination of IFN-α2b with ketoprofen improves the response to IFN in patients nonresponsive to IFN alone.